Conversion of clinically isolated syndrome to multiple sclerosis: a prospective multi-center study in Eastern India. Issue 2 (May 2019) - Banerjee, TK; Saha, M; Ghosh, E; Hazra, A; Das, A; Choudhury, D; Ojha, S; Haldar, A; Mukherjee, A; Nandi, SS; Ghosh, A; Mukherjee, A; et al.
Background: In White populations more than 60% of clinically isolated syndrome (CIS) convert to multiple sclerosis (MS) on a long-term follow-up; several predictors for conversion have been identified. Objective: This study aimed to determine the conversion rate and the predictors of conversion from CIS to MS (McDonald 2010) among Indians. The other objective was to evaluate the diagnostic accuracy of the new McDonald 2017 criteria in prediction of a second clinical attack. Methods: Clinical and demographic data of CIS cohorts were collected. Baseline investigations included cerebrospinal magnetic resonance imaging (MRI) with contrast and cerebrospinal fluid (CSF) testing for oligoclonal band (OCB). Follow-up clinical and MRI examinations were performed annually for at least 24 months. Results: Of the 82 subjects (age range 15–58 years), 36 (43.9%) converted to MS; 31/82 (37.8%) converted in 24 months. The predictors for conversion were earlier age of onset, CSF-OCB, cerebral MRI T2 lesion count, and periventricular and juxtacortical location of lesions. Twenty-two (26.83%) CIS fulfilled the McDonald MS 2017 criteria at baseline. Conclusion: In this first prospective study of CIS in India, the risk factors for conversion are similar but the conversion rate to MS is lower than that in the western nations.